Synergistic effect in alignment between business environment scanning strategy and IT strategy in enterprises - Jelonek,Dorota (2013)
This paper aims to confirm the hypothesis of synergistic effect of alignment of business environment scanning strategy with IT strategy on market performance in large and medium-sized enterprises in Poland. A model of alignment of the strategies of business environment scanning and IT in the enterprises was used to verify the following hypothesis: “Alignment between business environment scanning strategy and IT strategy affects market performance in the enterprise more significantly compared to these strategies considered individually”. The paper is divided into two parts. Firstly, it briefly reviews the literature regarding alignment, business environment scanning and IT. Secondly, a conceptual model of strategic alignment of business environment scanning strategy with IT strategy is presented and verified.